2018
DOI: 10.1016/j.cbpra.2017.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Development and Preliminary Feasibility Study of a Brief Behavioral Activation Mobile Application (Behavioral Apptivation) to Be Used in Conjunction With Ongoing Therapy

Abstract: Depressive symptoms are the most frequently treated psychiatric condition in the United States. Brief behavioral activation treatment for depression (BATD) is a popular, evidence-based psychotherapy with strong research support for the treatment of depression. In this paper, we describe the development and initial pilot feasibility testing of a BATD mobile application (Behavioral Apptivation) to be used by patients and therapists in conjunction with BATD therapy. We present information regarding the app develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 28 publications
0
20
0
1
Order By: Relevance
“…CSE is positively associated with psychological thriving (Sirois & Hirsch, 2013) and negatively associated with depression (Philip, Merluzzi, Zhang, & Heitzmann, 2013 and overall psychological distress (Benka et al, 2014;Pritchard & Gow, 2012;Smith, Benight, & Cieslak, 2013). While the outcomes of using some CBT-based MHapps have been studied (Dahne, Kustanowitz, & Lejuez, 2017;e.g., Huguet et al, 2016), the role of improving CSE to elicit mental health benefits remains unclear. Kuhn et al (2017) conducted a Randomised Controlled Trial (RCT) comparing the "PTSD Coach" app, for Post Traumatic Stress Disorder, to a waitlist condition over 3 months of treatment.…”
Section: Apps Like Moodmission May Prevent Depressive and Anxietymentioning
confidence: 99%
See 1 more Smart Citation
“…CSE is positively associated with psychological thriving (Sirois & Hirsch, 2013) and negatively associated with depression (Philip, Merluzzi, Zhang, & Heitzmann, 2013 and overall psychological distress (Benka et al, 2014;Pritchard & Gow, 2012;Smith, Benight, & Cieslak, 2013). While the outcomes of using some CBT-based MHapps have been studied (Dahne, Kustanowitz, & Lejuez, 2017;e.g., Huguet et al, 2016), the role of improving CSE to elicit mental health benefits remains unclear. Kuhn et al (2017) conducted a Randomised Controlled Trial (RCT) comparing the "PTSD Coach" app, for Post Traumatic Stress Disorder, to a waitlist condition over 3 months of treatment.…”
Section: Apps Like Moodmission May Prevent Depressive and Anxietymentioning
confidence: 99%
“…Apps like MoodMission may prevent depressive and anxiety disorders and serve as an adjunct to clinical treatments. While the outcomes of using some CBT-based MHapps have been studied (Dahne, Kustanowitz, & Lejuez, 2017;e.g., Huguet et al, 2016), the role of improving CSE to elicit mental health benefits remains unclear. CSE is positively associated with psychological thriving (Sirois & Hirsch, 2013) and negatively associated with depression (Philip, Merluzzi, Zhang, & Heitzmann, 2013 and overall psychological distress (Benka et al, 2014;Pritchard & Gow, 2012;Smith, Benight, & Cieslak, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Providing a list of suggested activities to the participant was also used in other apps based on behavioral activation to lower depressive symptoms [67,68]. Previous behavioral activation research suggested a list of 11 activity categories in which patients could start doing activities [66].…”
Section: Methodsmentioning
confidence: 99%
“…Although in-person interventions based on behavioral activation usually have a duration of 5 to 12 weekly sessions, with each session lasting approximately 45 min [69,70], interventions using technology need to deliver the core elements of the treatment by adapting them to the interface used and not as a mere copy of the content [71]. Other mobile interventions using behavioral activation were typically designed for a duration of 8 to 10 weekly sessions but were also accompanied with weekly psychotherapy sessions [67,68] or pharmacotherapy [72]. Considering the nurse accompanying the CONEMO intervention would only give technical support and that app developers recommend designing interventions of “high frequency, low intensity, and shorter time commitment” [71], it was decided to include 18 sessions in total, delivered 3 times a week over a period of 6 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…BAT-D is a promising treatment approach for a targeted mHealth smoking cessation intervention because it has shown promise helping smokers with depressive symptoms quit smoking in the face-to-face format [9,13], its components are well suited to translation into an app (eg, scheduling valued activities and tracking their completion), and it has a strong foundation in behavioral theory [11]. Indeed, other groups have begun developing and testing BAT-D apps for depression either to be used in conjunction with therapist support [18,19] or in self-guided format and designed for a primary care context [20,21]. With the most advanced evaluation of a BAT-D app to date being pilot RCTs not adequately powered to test efficacy [18,22,23] and the remainder of the published work limited to intervention descriptions or single-arm feasibility studies [19-21], there remains much to be learned about how to effectively translate BAT-D principles into mHealth interventions.…”
Section: Introductionmentioning
confidence: 99%